ANALISIS JALUR DISTRIBUSI PENJUALAN BUAH JERUK SIAM (Citrus nobilis) DI DESA TARO, KECAMATAN TEGALALANG, KABUPATEN GIANYAR - Dwitama, Prasetya; Suryawan Wiranatha, A.A.P. Agung; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 3 No 1 (2015): Maret, 2015)
This research aims to find out the types and the number of distribution channelsof the oranges from the farmers to consumers, and to compare the marketing and profit margins of all distribution channels. The population of this research was all farmers at “Gunung Mekar” farmers group and “Puncak Andong” farmers group, the collectors, retailers, and wholesalers. The sample of this research was taken by using purposive sampling method with 50% of the population. Data was taken by doing the survey in Taro village, and also the traditional markets, fruit store and supermarket in Denpasar. Data was analyzed by using both qualitative and quantitative methods. Qualitative analysis aims to find out the types and the number of distribution channels, and quantitative analysis aims to calculate the marketing and the profit margins from each distribution channel. The results showed that the distribution channel used was: producer – collectors – wholesalers – retailers. There are five distribution channels of the orange marketing from Taro village to the consumers in which the line ends in traditional markets, and there is another one in which it ends in the store and supermarket in Denpasar. The lowest marketing and profit margin was found in the second distribution channel (Sukawati market) which went through the collector with the marketing margin of Rp. 3,400/kg (54.84%) and the profit margin of Rp 2,450/kg (39.52%). While the highest marketing and profit margin was in the first distribution channel which went to Tiara Dewata supermarket with the marketing margin of Rp. 9,400/kg (151.61%) and the profit margin of Rp 5,483/kg (88.44%)
Keywords: 35